Behavior Of MSMES Around The Campus In The City Of Malang During The Covid-19 Pandemic And Their Relationship With The Implementation Of Economic Education - Adillia Risky Cahyaningtyas; Sri Umi Mintarti Widjaja; Agung Haryono (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The occurrence of the COVID-19 pandemic which began in March 2020 made many students return to their hometowns, thus crippling the economic activities of MSME owners in Malang City, especially the owners of food stalls around campus. To get around this, the food stall owners implement certain strategies to be able to maintain the continuity of their business in the midst of the sluggish economy due to the pandemic. The strategies applied by each owner of the food stalls vary depending on the economic education obtained either from the family, from the community, or from formal educational institutions. This research uses a qualitative approach to the type of phenomenology. The research location is around the MaIang City campus. Selection of informants using purposive technique. The data collection technique was carried out by interview, observation, and documentation. RESEARCH RESULTSshows thatIn maintaining business continuity in the midst of a pandemic, food stall owners around campus have two strategies, namely those who continue to sell by saving expenses, reducing the amount of food sold compared to before the pandemic, temporarily laying off employees, and so on. There are also those who choose not to sell for a while because of the quiet conditions of the stalls and to comply with government regulations so that the spread of covid can be suppressed. The economic education obtained by food stall owners includes financial recording and planning, saving routines, and investment. When food stall owners have these four components of economic education, they will most likely save the business they have built in the midst of the COVID-19 pandemic.